2017
DOI: 10.1016/j.apcatb.2016.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Graphitic-C3N4 hybridized N-doped La2Ti2O7 two-dimensional layered composites as efficient visible-light-driven photocatalyst

Abstract: a b s t r a c tPerovskite-type La 2 Ti 2 O 7 (LTO), having a layered structure and the separated H 2 and O 2 evolution sites, is attractive as an efficient photocatalyst. However, the photocatalytic activity is often limited by the poor electron mobility. This problem can be conquered by hybridization with materials having efficient properties for the visible light absorption and charge carrier transport. Here, we report a two-dimensional (2D) layered composite hybridized by approximately 2 nm thick graphitic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(43 citation statements)
references
References 46 publications
(45 reference statements)
1
42
0
Order By: Relevance
“…Some perovskite-type 2D semiconductors with a hexagonal crystal structure can also be coupled with 2D g-C 3 N 4 to form a 2D/2D Type-II photocatalyst for photocatalytic hydrogen evolution. Cai et al [105] reported the hybridization of 7 nm thick N-doped La 2 Ti 2 O 7 (NLTO) nanosheets with 2 nm thick g-C 3 N 4 nanosheets to construct a g-C 3 N 4 /NLTO composite with a Type-II band alignment, in which the g-C 3 N 4 and NLTO respectively act as hole receptor and electron conductor. As a result, the optimal g-C 3 Z-scheme 2D/2D photocatalysts (Fig.…”
Section: Hydrogen Generationmentioning
confidence: 99%
“…Some perovskite-type 2D semiconductors with a hexagonal crystal structure can also be coupled with 2D g-C 3 N 4 to form a 2D/2D Type-II photocatalyst for photocatalytic hydrogen evolution. Cai et al [105] reported the hybridization of 7 nm thick N-doped La 2 Ti 2 O 7 (NLTO) nanosheets with 2 nm thick g-C 3 N 4 nanosheets to construct a g-C 3 N 4 /NLTO composite with a Type-II band alignment, in which the g-C 3 N 4 and NLTO respectively act as hole receptor and electron conductor. As a result, the optimal g-C 3 Z-scheme 2D/2D photocatalysts (Fig.…”
Section: Hydrogen Generationmentioning
confidence: 99%
“…As a typical metal‐free semiconductor, g‐C 3 N 4 has been extensively applied in photocatalytic fields for the degradation of pollutants, H 2 production, and CO 2 reduction due to its characteristics of moderate bandgap (≈2.7 eV), low cost, nontoxicity, good stability, easy preparation, and suitable electronic band structure . Since g‐C 3 N 4 was first reported for the photocatalytic H 2 evolution by Wang et al, much attention has been paid to improve the photocatalytic activity by combining g­C 3 N 4 with other 2D TNMOs such as KTiNbO 5 , HCa 2 Nb 3 O 10 , KCa 2 Nb 2 TaO 10 , N‐doped La 2 Ti 2 O 7 , 2D TiO 2 NSs, and SnNb 2 O 6 NS …”
Section: Enhanced Photocatalytic Activity With Modificationmentioning
confidence: 99%
“…Generally, the photocatalytic activity of a porous 2D structure would be higher than that of the well‐ordered intercalation structure due to the accessibility of protons to the reaction sites. Recently, 2D TNMO NSs such as HCa 2 Nb 3 O 10 , KCa 2 Nb 2 TaO 10 , and N‐doped La 2 Ti 2 O 7 , were incorporated with g‐C 3 N 4 NSs to construct a series of layered heterojunctions via a facile exfoliation–reassembly process . The resultant composites showed an intimate interfacial contact between two components, resulting in the efficient photoexcited charge transfer and simultaneously decreased charge recombination rate.…”
Section: Enhanced Photocatalytic Activity With Modificationmentioning
confidence: 99%
“…Most recently, perovskite-type nitrogen-doped La2Ti2O7 (NLTO), comprising a 2D architecture with a thickness of 7 nm, was for the first time hybridized with 2 nm thick g-C3N4 nanosheets by means of a facile two-step hydrothermal method and a thermal treatment process ( Figure 4A) (Cai et al, 2017). The hybrid layered nanomaterials showed excellent photocatalytic H2 evolution with a high apparent quantum efficiency of 2.1% at 400 nm.…”
Section: Hybridization With 2d Metal Oxidesmentioning
confidence: 99%